'Pulmonary thrombosis in situ': risk factors, clinic characteristics and long-term evolution. Issue 7 (October 2020) - Fletcher-Sanfeliu, Delfina; Redón, Josep; García-Granero, Álvaro; Frasson, Matteo; Barreira, Ignacio; Martínez-León, Juan; García-Fuster, María J.
Abstract : N/A: Pulmonary embolism typically occurs from deep venous thrombosis (DVT). However, not always a DVT can be identified, and 'in situ ' generation of pulmonary embolism has been considered, referred to in the literature as 'De novo pulmonary embolism' (DNPE). The objective of the study is to assess risk factors, comorbidities, clinic characteristics and long-term evolution of patients with pulmonary embolism in the absence of an identified source. Retrospective study of 280 patients with pulmonary embolism, 190 pulmonary embolisms with DVT group and 90 (32%) pulmonary embolism without DVT (DNPE group), admitted to an Internal Medicine Department of a tertiary hospital from January 2012 to December 2015. In the DNPE group, segmental and subsegmental arteries were more frequently affected ( P = 0.01). As compared with pulmonary embolisms with DVT group: older age, female sex, sedentary lifestyle, diabetes mellitus, arterial hypertension, heart failure, respiratory infections and chronic obstructive pulmonary disease (COPD) were significantly more frequent in DNPE. In multivariate analysis, respiratory infection [odds ratio (OR) 12.2, P < 0.0001], COPD (OR 8.7, P < 0.0001) and female sex (OR 3.0, P = 0.003) were independently associated risk factors. Long-term mortality (median follow-up 15 months) was also higher in DNPE group (34 vs. 16%, P = 0.01). De novo pulmonary embolism occurred in 32% of cases of pulmonary embolisms and was more frequent in female and COPD patients or those with respiratory infections as compared with pulmonary embolisms in which DVT was identified as a source of embolism.